Primary Spinal Epidural Abscesses Not Associated With Pyogenic Infectious Spondylodiscitis: A New Pathogenetic Hypothesis - Magrassi, Lorenzo; Mussa, Marco; Montalbetti, Andrea; Colaneri, Marta; di Matteo, Angela; Malfitano, Antonello; Simoncelli, Anna Maria; Egitto, Maria Grazia; Bernucci, Claudio; Brunetti, Enrico (Frontiers in Surgery, 2020)
Introduction: Spinal epidural abscess (SEAs) incidence is rising. However, most series do not differentiate between SEAs associated with pyogenic infectious spondylodiscitis (PS) and SEAs limited to the epidural space. Methods: We retrospectively reviewed the records and radiological images of all patients admitted to our institutions with a diagnosis of SEAs not associated with PS between January 2013 and December 2018. Results: We found 3 males and 4 females, 5 of 7 were intravenous drug users. All patients presented with pain, in 6 associated with acute motor and sensory deficits while one, had only pain and paresthesias. Staphylococcus aureus was cultured from abscesses and/or from multiple blood cultures in four patients. Abscesses were localized to the cervical spine in 1 patient, thoracic in 3, lumbar in 1, and in 2 the SEAs involved multiple segments. All patients but one underwent urgent open surgery. This patient had a multisegmental abscess and was successfully treated by percutaneous aspiration when pain became intractable. After abscess evacuation the neurological deficits improved in all patients except one. The patients that were treated without spine instrumentation did not develop delayed kyphosis or instability at follow-up. Conclusion: Patients with SEAs not associated with PS are likely to present with pain and motor deficits, appear to benefit from urgent abscess evacuation and seem to be less dependent on spine instrumentation to avoid delayed spinal deformities compared to SEA associated with PS. Finally, the lack of initial involvement of bone and intervertebral disks may suggest that at least some of the SEA without PS originate from infection of epidural lymphatic vessels that are not present inside those structures.